Association of Antenatal Corticosteroid Exposure and Infant Survival at 22 and 23 Weeks - Rossi, Robert M.; DeFranco, Emily A.; Hall, Eric S. (American Journal of Perinatology, 2021)
Objective In 2014, the leading obstetric societies published an executive summary of a joint workshop to establish obstetric interventions to be considered for periviable births. Antenatal corticosteroid administration between 220/7 and 226/7 weeks was not recommended given existing evidence. We sought to evaluate whether antenatal steroid exposure was associated with improved survival among resuscitated newborns delivered between 22 and 23 weeks of gestation.Study Design We conducted a population-based cohort study of all resuscitated livebirths delivered between 220/7 and 236/7 weeks of gestation in the United States during 2009 to 2014 utilizing National Center for Health Statistics data. The primary outcome was rate of survival to 1 year of life (YOL) between infant cohorts based on antenatal steroid exposure. Multivariable logistic regression estimated the association of antenatal steroid exposure on survival outcomes.Results In the United States between 2009 and 2014, there were 2,635 and 7,992 infants who received postnatal resuscitation after delivery between 220/7 to 226/7 and 230/7 to 236/7 weeks of gestation, respectively. Few infants born at 22 (15.9%) and 23 (26.0%) weeks of gestation received antenatal corticosteroids (ANCS). Among resuscitated neonates, survival to 1 YOL was 45.2 versus 27.8% (adjusted relative risk [aRR]: 1.6, 95% confidence interval [CI]: 1.2–2.1) and 57.9 versus 47.7% (aRR: 1.3, 95% CI: 1.1–1.5) for infants exposed to ANCS compared with those not exposed at 22 and 23 weeks of gestation, respectively. When stratified by 100 g birth weight category, ANCS were associated with survival among neonates weighing 500 to 599 g (aRR: 1.9, 95% CI: 1.3–2.9) and 600 to 699 g (aRR: 1.7, 95% CI: 1.1–2.6) at 22 weeks.Conclusion Exposure to ANCS was associated with higher survival rates to 1 YOL among resuscitated infants born at 22 and 23 weeks. National guidelines recommending against ANCS utilization at 22 weeks should be re-evaluated given emerging evidence of benefit.Key Points
Keywords: periviable birth; antenatal corticosteroids; infant survival